Sex Differentiation and Long‐Distance Gene Flow in the Elusive Antarctic Fish Aethotaxis mitopteryx - Luca Schiavon; Thomas Desvignes; Fabrizia Ronco; Michael Matschiner; Martina Gastaldi; Thore Koppetsch; Audun Schrøder‐Nielsen; John H. Postlethwait; Alessia Prestanti; Federica Stranci; Santiago G. Ceballos; Felix C. Mark; et al. (Ecology and Evolution)
ABSTRACT Understanding population connectivity in the marine realm is crucial for conserving biodiversity, managing fisheries, and predicting species responses to environmental change. This is particularly important in Antarctic waters, where unique evolutionary histories and extreme conditions shape marine biodiversity. The longfin icedevil Aethotaxis mitopteryx is an elusive notothenioid fish endemic to Antarctic waters. To explore population connectivity in A. mitopteryx, we used RAD‐seq to investigate the genetic differentiation of two populations, one from the Eastern Weddell Sea and the other from the Eastern Antarctic Peninsula, two regions of ecological relevance greatly impacted by climate change. Despite spatial separation, analyses revealed no significant genetic differentiation between the two populations, suggesting extensive gene flow. A pronounced genetic distinction was, however, observed between males and females. This differentiation was largely localized to a specific chromosome, implying a genetic sex determination system with males being the heterogametic sex. These findings contribute novel insights into the genetic structure of A. mitopteryx populations and expand our understanding of genetic mechanisms in Antarctic fish. This study provides a foundation for further investigations into the evolutionary and ecological implications of sex chromosome differentiation in extreme environments.